AUV-based acoustic observations of the distribution and patchiness of pelagic scattering layers during midnight sun - Geoffroy, Maxime; Cottier, Finlo Robert; Berge, Jørgen; Inall, Mark E. (ICES Journal of Marine Science, 2016)
Manuscript. Published version available in ICES J Mar Sci 2016 fsw158. doi:10.1093/icesjms/fsw158 An autonomous underwater vehicle (AUV) carrying 614 kHz RDI acoustic doppler current profilers (ADCPs) was deployed at four locations over the West Spitsbergen outer shelf in July 2010. The backscatter signal recorded by the ADCPs was extracted and analysed to investigate the vertical distribution and patchiness of pelagic organisms during midnight sun. At the northernmost locations (Norskebanken and Woodfjorden), fresher and colder water prevailed in the surface layer (0–20 m) and scatterers (interpreted as zooplankton and micronekton) were mainly distributed below the pycnocline. In contrast, more saline and warmer Atlantic Water dominated the surface layer at Kongsfjordbanken and Isfjordbanken and scatterers were concentrated in the top 20 m, above the pycnocline. Pelagic scatterers formed patchy aggregations at all locations, but patchiness generally increased with the density of organisms and decreased at depths >80 m. This study contributes to our understanding of the vertical distribution of pelagic organisms in the Arctic, and the spatial coverage of the AUV has extended early acoustic studies limited to Arctic fjords from 1D observations to a broader offshore coverage. Neither synchronized nor unsynchronized vertical migrations were detected, but autonomous vehicles with limited autonomy (<1 day) may not be as effective as long-term mooring deployments or long-range AUVs to study vertical migrations. Short-term AUV-based acoustic surveys of the pelagic communities are nonetheless highly complementary to Eulerian studies, in particular by providing spatial measurements of patchiness. Compared with ship-based or moored acoustic instruments, the 3D trajectory of AUVs also allows using acoustic instruments with higher frequencies and better size resolution, as well as the detection of organisms closer to the surface.